2019
DOI: 10.1093/heapol/czz028
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of training in emergency obstetric care: a systematic literature review

Abstract: Providing quality emergency obstetric care (EmOC) reduces the risk of maternal and newborn mortality and morbidity. There is evidence that over 50% of maternal health programmes that result in improving access to EmOC and reduce maternal mortality have an EmOC training component. The objective was to review the evidence for the effectiveness of training in EmOC. Eleven databases and websites were searched for publications describing EmOC training evaluations between 1997 and 2017. Effectiveness was assessed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 99 publications
2
83
0
6
Order By: Relevance
“…Several reviews have highlighted the active components of effective emergency obstetric training including: institution-level incentives to training; regular, multiprofessional, mandatory, ‘in house’ training; teamwork training integrated with clinical teaching; and the use of on-site high-fidelity simulation models,20 21 but in some studies, training for obstetric emergencies is not always found to be effective in terms of measurable change in clinical outcomes 22 23. However, a recent systematic review investigating the effectiveness of training in emergency obstetric care found strong evidence for improved clinical practice in areas such as adherence to protocols, resuscitation technique, communication and teamwork, as well as improved neonatal outcomes such as reduced trauma after shoulder dystocia 24. It did not, however, find strong evidence for a reduction in other outcomes such as postpartum haemorrhage, maternal death and stillbirth rates 24.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reviews have highlighted the active components of effective emergency obstetric training including: institution-level incentives to training; regular, multiprofessional, mandatory, ‘in house’ training; teamwork training integrated with clinical teaching; and the use of on-site high-fidelity simulation models,20 21 but in some studies, training for obstetric emergencies is not always found to be effective in terms of measurable change in clinical outcomes 22 23. However, a recent systematic review investigating the effectiveness of training in emergency obstetric care found strong evidence for improved clinical practice in areas such as adherence to protocols, resuscitation technique, communication and teamwork, as well as improved neonatal outcomes such as reduced trauma after shoulder dystocia 24. It did not, however, find strong evidence for a reduction in other outcomes such as postpartum haemorrhage, maternal death and stillbirth rates 24.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent systematic review investigating the effectiveness of training in emergency obstetric care found strong evidence for improved clinical practice in areas such as adherence to protocols, resuscitation technique, communication and teamwork, as well as improved neonatal outcomes such as reduced trauma after shoulder dystocia 24. It did not, however, find strong evidence for a reduction in other outcomes such as postpartum haemorrhage, maternal death and stillbirth rates 24. Further, a large randomised controlled trial of PROMPT (PRactical Obstetric Multi-Professional Training) which included over 87 000 births in Scotland, published after the systematic review, found no improvement in neonatal outcomes (measured by the number of infants with an Apgar score of less than 7 at 5 minutes) 25…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that short and competency-based 'in-service' training in emergency obstetric care results in signi cant improvements in healthcare provider competence and a move to making better use of guidelines (37).In addition, training at the start of implementation and continuing education throughout the implementation process is to be recommended to increase the use of guidelines (38). Lack of up-todate training opportunities was identi ed as a constraint that hinders the full implementation of guideline use in our present study which is concurrent with a previous study done in Mozambique (11).Participants reported differences in in knowledge of existing ANC guidelines..…”
Section: Discussionmentioning
confidence: 99%
“…The use of simulators and simulation environments for teaching health professionals is well established in the literature (5,(7)(8) . Although the quality of studies is heterogeneous and with several different indicators, evidence has shown that simulation-based teaching is effective and leads to better and more lasting results than traditional teaching (7,9) .…”
Section: Givenmentioning
confidence: 99%